Applying an Augmented Reality as an Android-Based Tajweed Science Learning Media - Sari, Linda (Journal of Engineering, Technology, and Applied Science (JETAS), 2022)
Augmented Reality sesuai digunakan untuk membuat media pembelajaran yang menarik. Ada pun tujuan dari penelitian ini adalah membuat media pembelajaran Ilmu Tajwid bisa terbuat dengan menggunakan teknologi Augmented Reality yang diditerapkan ke dalam fitur mobile Android. Tujuan pembuatan media pembelajaran ini adalah untuk meningkatkan mutu ketaqwaan pada Allak SWT, mewujudkan tanggung jawab seseorang mukmin kepada Al-Quran, membawakan seseorang mukmin membaca Al-Quran dengan ber-Tajwid, menolong warga pemeluk mukmin berlatih Ilmu Tajwid tanpa wajib menghadiri kursus serta dapat berlatih dimanapun serta kapanpun. Kesimpulan dari penelitian ini adalah dengan memakainya aplikasi AR pengguna lebih menguasai Ilmu Tajwid tanpa terikat durasi waktu serta tempat, dan pengguna lebih atensi serta terpikat dalam berlatih Ilmu Tajwid. Applying an Augmented Reality as an Android-Based Tajweed Science Learning Media Abstract: Augmented Reality is suitable to be used to create interesting learning media. The purpose of this research is to make Tajweed Science learning media can be made using Augmented Reality technology which is applied to Android mobile features. The purpose of making this learning media is to improve the quality of piety to Allah SWT, realize the responsibility of a believer to the Al-Quran, bring a believer to read the Qur'an with Tajweed, help believers practice Tajweed without having to attend courses and can practice wherever and whenever. The conclusion of this study is that by using the AR application, users are more familiar with Tajweed Science without being bound by the duration of time and place, and users are more attentive and captivated in practicing Tajweed Science. Keywords: Augmented Reality, Learning Media, Tajweed. Applying an Augmented Reality as an Android-Based Tajweed Science Introduction Media Abstract: The Tajweed Science upgrading tool can be made using Augmented Reality technology which is applied to Android mobile features. The purpose of this research is to improve the quality of piety to Allah SWT, to realize the responsibility of a believer to the Qur'an, to bring a believer to read the Qur'an with Tajweed, to help believers practice Tajweed without having to attend courses and to be able to practice anywhere and anytime. The conclusion of this study is that by using the AR application, users are more familiar with Tajweed Science without being bound by the duration of time and place, and users are more attentive and captivated in practicing Tajweed Science. Keywords: Augmented Reality, Learning Media, Tajweed.